A review study on proton exchange membrane fuel cell electrochemical performance focusing on anode and cathode catalyst layer modelling at macroscopic level. (November 2021) - Tzelepis, Stefanos; Kavadias, Kosmas A.; Marnellos, George E.; Xydis, George
Abstract: Fuel cells are promising energy conversion devices exhibiting high electrical efficiencies and zero emissions when green hydrogen is employed as a fuel feedstock, with applications in both the mobility and stationary sectors. This paper presents a comprehensive review on anode and cathode layer macroscopic modelling studies for proton exchange membrane fuel cells (PEMFCs) that incorporate in a coupled manner both the electrochemical and transport (mass, heat and momentum) phenomena taking place at each compartment. The reviewed models have been classified according to their spatial dimensions into one-dimensional, two-dimensional and three-dimensional, giving particular emphasis on the examination of both catalyst layers. For each examined case, valuable information is provided regarding the modelling technique applied, the assumptions that have been made, and the validation procedure followed. This review includes essential information regarding the suitability of each simulation method to understand the impact of electro-catalysts' physicochemical properties on the overall PEMFC electrochemical performance. In this sense, the requirement to simulate PEMFCs operation by investigating several alternative electrode material composites is underlined to provide a credible pathway to improve cell performance and minimize or even eliminate the incorporation of costly materials such as platinum or platinum group metals (PGM) in the anode and cathode electrodes. Highlights: Review of macroscopic models simulating PEMFCs, emphasizing on catalyst layers. Modelling strategies for developing a PEMFC model. Investigation of new electrodes composites for both anode and cathode catalyst layers.